Piezo2 Knockdown Inhibits Noxious Mechanical Stimulation and NGF-Induced Sensitization in A-Delta Bone Afferent Neurons - Nencini, Sara; Morgan, Michael; Thai, Jenny; Jobling, Andrew I.; Mazzone, Stuart B.; Ivanusic, Jason J. (Frontiers in Physiology, 2021)
Piezo2 is a mechanically gated ion-channel that has a well-defined role in innocuous mechanical sensitivity, but recently has also been suggested to play a role in mechanically-induced pain. Here we have explored a role for Piezo2 in mechanically evoked bone nociception in Sprague Dawley rats. We have used an in vivo electrophysiological bone-nerve preparation to record the activity of single Aδ bone afferent neurons in response to noxious mechanical stimulation, after Piezo2 knockdown in the dorsal root ganglia with intrathecal injections of Piezo2 antisense oligodeoxynucleotides, or in control animals that received mismatch oligodeoxynucleotides. There were no differences in the number of Aδ bone afferent neurons responding to the mechanical stimulus, or their threshold for mechanical activation, in Piezo2 knockdown animals compared to mismatch control animals. However, bone afferent neurons in Piezo2 knockdown animals had reduced discharge frequencies and took longer to recover from stimulus-evoked fatigue than those in mismatch control animals. Piezo2 knockdown also prevented NGF-induced sensitization of bone afferent neurons, and retrograde labelled bone afferent neurons that expressed Piezo2 co-expressed TrkA, the high affinity receptor for nerve growth factor (NGF). Our findings demonstrate that Piezo2 contributes to the response of bone afferent neurons to noxious mechanical stimulation, and plays a role in processes that sensitize them to mechanical stimulation.